Improving diabetes care for people with intellectual disabilities: a qualitative study exploring the perceptions and experiences of professionals in diabetes and intellectual disability services. Issue 5 (28th February 2017) - Brown, M.; Taggart, L.; Karatzias, T.; Truesdale, M.; Walley, R.; Northway, R.; Macrae, S.; Carey, M.; Davies, M.
Abstract: Background: Globally, diabetes is increasing with concerns about the impact on outcomes, including premature death and the costs associated with managing the condition. Research indicates that adults with intellectual disabilities (ID) are two to three times more likely to develop diabetes; however, there has been limited focus on diabetes service utilisation in this population. The aim of this study is to explore the perceptions and experiences of diabetes and ID practitioners. Methods: A series of 1:1 semi‐structured interviews were undertaken in one Scottish health service area. In total, 29 qualitative interviews were conducted: 10 with diabetes practitioners from primary and secondary care, 14 from ID services and 5 from community care services regarding diabetes service provision for this population. Thematic content analysis was undertaken to identify the themes and subthemes. Results: Three main themes were identified: (1) enabling access to services to meet diabetes‐related care needs of people with ID; (2) communication and service improvements between staff, patients and across services; and (3) providing person‐centred diabetes care and developing adapted resources to increase patient self‐care. Conclusions: The findings of this study have important international implications in how diabetes practitioners plan and deliver services for people with ID and other vulnerable groups with limited cognitive ability and communication skills and difficulties in self‐management. The findings highlight that access to diabetes education and adapted resources is needed, and if 'reasonable adjustments' are made to service provision and practice, people with ID can benefit from improved healthcare. Developing joint clinics to share knowledge and resources between diabetes and ID practitioners may improve service delivery and continuity of care, and thereby diminish the costs of not providing quality care.